PO 23 - IATROGENIC TRACHEOBRONCHIAL RUPTURE IN A FRAGILE PATIENT - Beatriz Carvalho Gonçalves1,; João Abreu1,; Ricardo Rodrigues1,; Karina Gama1,; Mariana Luís1, (Journal of the Portuguese Society of Anesthesiology, 2023)
.